Impact of Isometric Contraction of Anterior Cervical Muscles on Cervical Lordosis - Fedorchuk, Curtis A (J Radiol Case Rep, 2016)
OBJECTIVE: This study investigates the impact of isometric contraction of anterior cervical muscles on cervical lordosis. METHODS: 29 volunteers were randomly assigned to an anterior head translation (n=15) or anterior head flexion (n=14) group. Resting neutral lateral cervical x-rays were compared to x-rays of sustained isometric contraction of the anterior cervical muscles producing anterior head translation or anterior head flexion. RESULTS: Paired sample t-tests indicate no significant difference between pre and post anterior head translation or anterior head flexion. Analysis of variance suggests that gender and peak force were not associated with change in cervical lordosis. Chamberlain’s to atlas plane line angle difference was significantly associated with cervical lordosis difference during anterior head translation (p=0.01). CONCLUSION: This study shows no evidence that hypertonicity, as seen in muscle spasms, of the muscles responsible for anterior head translation and anterior head flexion have a significant impact on cervical lordosis.